2010
DOI: 10.1007/s11661-010-0344-x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Stability of Equiatomic and Nonequiatomic Nanocrystalline CuNiCoZnAlTi High-Entropy Alloys by Mechanical Alloying

Abstract: Nanocrystalline equiatomic high-entropy alloys (HEAs) have been synthesized by mechanical alloying in the Cu-Ni-Co-Zn-Al-Ti system from the binary CuNi alloy to the hexanary CuNiCoZnAlTi alloy. An attempt also has been made to find the influence of nonequiatomic compositions on the HEA formation by varying the Cu content up to 50 at. pct (Cu x NiCoZnAlTi; x = 0, 8.33, 33.33, 49.98 at. pct). The phase formation and stability of mechanically alloyed powder at an elevated temperature (1073 K [800°C] for 1 hour) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 19 publications
1
30
0
10
Order By: Relevance
“…HEA powders can be prepared by ball milling. [98,[127][128][129][130][131] The powders can subsequently be sintered to form bulk HEAs with ultrafine structure. [98,127,129] Single-crystal of the Al 0.3 CoCrFeNi HEA has also been prepared successfully by the Bridgman solidification method.…”
Section: Corrosion Propertiesmentioning
confidence: 99%
“…HEA powders can be prepared by ball milling. [98,[127][128][129][130][131] The powders can subsequently be sintered to form bulk HEAs with ultrafine structure. [98,127,129] Single-crystal of the Al 0.3 CoCrFeNi HEA has also been prepared successfully by the Bridgman solidification method.…”
Section: Corrosion Propertiesmentioning
confidence: 99%
“…4 has clearly indicated that the phase has BCC structure. Similarly equiatomic binary AlFe [9], ternary AlFeTi, quaternary AlFeTiCr and the quinary AlFeTiCrZn nanocrystalline high entropy alloys have also been found to have BCC structure. The compacted AlFeTiCrZnCu alloy sintered at 800 • C for 1 h in an argon atmosphere has shown 99% density.…”
Section: Resultsmentioning
confidence: 96%
“…Fig. 3 shows the EDX spectrum [9] obtained from one of the powder particle in the hexanary AlFeTiCrZnCu high entropy alloy milled for 10 h. The nominal composition of each element in this alloy is 16.6 at.%, and the quantitative elemental analysis results from the EDX spectrum in Fig. 3 clearly indicate that the homogeneity and the equiatomic composition is maintained in each particle of the alloy after 20 h. The nanocrystalline nature of the high entropy alloy has been confirmed from the TEM bright field image and the corresponding selected area diffraction (SAD) pattern shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…V průmyslu jsou slitiny s vysokou entropií připravovány především technologií z kapalné fáze, konkrétně z taveniny. Další způsoby, které jsou uplatňovány pro výrobu těchto slitinových povlaků, jsou naprašování a mechanické legování [6][7][8][9][10][11].…”
Section: úVodunclassified
“…V průmyslu jsou slitiny s vysokou entropií připravovány především technologií z kapalné fáze, konkrétně z taveniny. Další způsoby, které jsou uplatňovány pro výrobu těchto slitinových povlaků, jsou naprašování a mechanické legování [6][7][8][9][10][11].Elektrochemická depozice je pro přípravu těchto speciálních povlaků využívána nejméně. V současnosti se elektrochemické nanášení slitinových povlaků s vysokou entropií provádí zejména z organických nevodných systémů, konkrétně z DMSO (dymetylsulfoxid) nebo ze směsi N,N-DMF (dimetylformamid), které jsou ovšem velmi citlivé na vzdušnou vlhkost.…”
unclassified